Posttraumatic stress disorder symptoms among Chinese college students following the COVID-19 outbreak - Wang, Jie-Yu; Li, Qi; Liu, Wei; Yang, Yang; Wang, Xiao-Guang; Liu, Chun-Yan; Shu, Xi-Ji; Xue, Li; Shi, Yan-Wei (Frontiers in Neuroscience, 2023)
Objective: This study examined the prevalence of posttraumatic stress disorder (PTSD) in college students one month after the COVID-19 outbreak to identify possible risk factors for PTSD symptoms in a cross-sectional study. Methods: Out of 10,502 who responded, 9,274 students impacted by the COVID-19 pandemic were included in our study. PTSD symptoms was evaluated by the Impact of Event Scale-revised (IES-R). Anxiety/depression symptoms were evaluated by the Kessler Psychological Distress Scale (K10). Personality traits, coping style and social support were assessed by the Eysenck Personality Questionnaire-Revised Short Scale for Chinese (EPQ-RSC), the Simplified Coping Style Questionnaire (SCSQ) and the Social Support Rating Scale (SSRS). Logistic regression analysis was utilized to further explore risk factors for PTSD symptoms. Results: More than one month after the COVID-19 outbreak, 13.1% of college students developed PTSD symptoms, indicating that COVID-19-associated stressful experiences were connected with PTSD. After the COVID-19 outbreak, subjects with symptomatologic PTSD symptoms were more likely to experience strained relationships with their family, to have close contact with COVID-19 patients and to drop out of college. The logistic regression model demonstrated the association factors of PTSD symptoms. Neuroticism, psychoticism and an avoidant coping style were associated with increased risk for PTSD symptoms, while an active coping style was protective against PTSD during this pandenmic. Conclusion: The results showed that PTSD was prevalent in Chinese college students one month after the COVID-19 outbreak. Effective psychological support work should be carried out accordingly.